1993
DOI: 10.2307/1940853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mineral Nutrition on Delayed Inducible Resistance in Alaska Paper Birch

Abstract: In subarctic forests, birch (Betula) trees respond to severe (50—100%) manual defoliation by delayed inducible resistance (DIR). This plant response to defoliation is characterized by a decline in the nutritional quality of leaves for immature insects for several years after defoliation events, and concomitant changes in leaf chemistry that may be detrimental to insect nutrition, that is, a decline in leaf nitrogen and an increase in leaf phenols. Two explanations of delayed inducible resistance have been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
91
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 32 publications
7
91
2
1
Order By: Relevance
“…Bryant et al [13] found that complete artificial defoliation of birch (Betula resinifera) increased tannin concentrations in plants in a low-nutrient treatment, but had no effect on those under high nutrients. Previous damage by gypsy moth populations increased phenolic concentration in unfertilized Quercus pinus foliage, but not in fertilized trees [40].…”
Section: Discussionmentioning
confidence: 99%
“…Bryant et al [13] found that complete artificial defoliation of birch (Betula resinifera) increased tannin concentrations in plants in a low-nutrient treatment, but had no effect on those under high nutrients. Previous damage by gypsy moth populations increased phenolic concentration in unfertilized Quercus pinus foliage, but not in fertilized trees [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the relationship between insect performance and plant chemistry have also reported varying results (Tija & Houston 1975;Zucker 1982;Waring & Price 1990;Hartley & Lawton 1992;Waring & Cobb 1992;Bryant et al 1993;Hartley & Jones 1997). Nevertheless, these studies generally found a positive relationship between insect performance and plant nitrogen content, and a negative relationship to secondary compounds (e.g.…”
Section: Key-words: Adelges Abietis Insect-plant Interactions Parabmentioning
confidence: 99%
“…reduced the pupal mass and survival of Rheumaptera hastata (L.) larvae. 52 It has been reported that induction of tannins in Populus tremuloides Michx. leaves in response to wound-and herbivore occurs by transcriptional activation of the flavonoid pathway.…”
mentioning
confidence: 99%